MicroRNA-146b Overexpression Promotes Human Bladder Cancer Invasion via Enhancing ETS2-Mediated mmp2 mRNA Transcription - Junlan Zhu; Chunxia Xu; Liming Ruan; Jianping Wu; Yang Li; Xingguo Zhang (Elsevier, 2019)
Although microRNAs have been validated to play prominent roles in the occurrence and development of human bladder cancer (BC), alterations and function of many microRNAs (miRNAs) in bladder cancer invasion are not fully explored yet. miR-146b was reported to be a tumor suppressor or oncomiRNA in various types of cancer. However, its accurate expression, function, and mechanism in bladder cancer remain unclear. Here we discovered that miR-146b was frequently upregulated in bladder cancer tissues compared with adjacent non-cancerous tissues. Inhibition of miR-146b resulted in a significant inhibitory effect on the invasion of bladder cancer cells by reducing mmp2 mRNA transcription and protein expression. We further demonstrated that knockdown of miR-146b attenuated ETS2 expression, which was the transcription factor of matrix metalloproteinase (MMP)2. Moreover, mechanistic studies revealed that miR-146b inhibition stabilized ARE/poly(U)-binding/degradation factor 1 (auf1) mRNA by directly binding to its mRNA 3' UTR, further reduced ets2 mRNA stability, and finally inhibited mmp2 transcription and attenuated bladder cancer invasion abilities. The identification of the miR-146b/AUF1/ETS2/MMP2 mechanism for promoting bladder cancer invasion provides significant insights into understanding the nature of bladder cancer metastasis. Targeting the pathway described here may be a novel approach for inhibiting invasion and metastasis of bladder cancer. Keywords: miR-146b, human bladder cancer invasion, MMP2, AUF1, ETS2